ANALISIS KUAT TEKAN DAN DENSITAS BETON NON-PASIR DENGAN CAMPURAN VARIAN ABU TERBANG MENGGUNAKAN MATLAB - Nahari Rasif; Indri Silvia Dewi; Nisya Aviani; Widya Utama (Jurusan Teknik Sipil, Politeknik Negeri Malang, 2020)
This study aims to determine how the properties of non-sand concrete with variations in the amount of mixing fly ash. This property was analyzed by compressive strength test. We also do calculations using the MATLAB application with interactive script methods. There are 16 numbers of test objects conducted in this study. The specimen is cylindrical with a size of 7.5 cm and a height of 15 cm. Flying ash variations used ranged from 0%, 25%, 50%, and 75%. In this research, we use 1: 6 between cement and gravel. The results of the average compressive strength obtained in the mixture of 0% fly ash are 1,172 MPa, 25% 0.871 MPa, 50% 2,367 MPa and 1,465 MPa for mixture of 75% fly ash. The best compressive strength results on the 50% fly ash mixture. The density is also affected by the mixing of this fly ash. The greater the mixing of the fly ash, the smaller the density value. Keywords: compressive strength, density, fly ash, MATLAB